(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This research explores the role of stylistic means in the formation of criminological units in English and Uzbek languages. It analyzes how linguistic and stylistic devices such as metaphors, euphemisms, jargon, and tone contribute to the construction of criminal discourse in both legal and media texts. The study also compares cross-cultural features and the stylistic representation of criminality in English and Uzbek, focusing on public perception and legal interpretation. The findings aim to contribute to forensic linguistics and the stylistic analysis of legal language.